Stay here with me a memoir - Olmstead, Robert 1954- (Metropolitan Books u.a., 1996)
Authentic, intimate, and intense, Stay Here with Me is about coming of age and leaving home, about the acts of rebellion that free the body even as they bind the soul to a place forever. Olmstead lays bare the acute pain of his father's alcoholism and the shattering decline of his grandfather, the family patriarch. With delicate sensuality, he traces the flowering of his love for a woman who "walks like light would walk if it could." And throughout, there is the land where his family has worked and lived and died for six generations, land at once richly abundant and cruelly demanding